Modelling to Assess the Role of Physico-chemical Attributes in Drying of Kikar [Acacia nilotica Linn. (Willd.)] Plantations in Punjab - Banyal, R.; Luna, R. K.; Kaushal, P. (Indian Forester, 2008)
In recent past, an unusual and large scale mortality of Kikar in almost all age-classes has been reported from every region of Punjab. The present study attempts to investigate the effect of physico-chemical attributes of the soil on this mortality. For this purpose four agroclimate zones covering 23 sites have been surveyed for detailed investigation and the results statistically analyzed to determine their individual and combined effect. The mortality ranges from 0.00 to 56.25% (average 42.25%) the highest being in block plantations. A single factor has not been found responsible for this mortality. It is rather the result of their acting in combination. Level of available phosphorus is found to contribute maximum effect. It is observed that existing levels of organic carbon, pH, electrical conductivity, water holding capacity of the soil and availability of nitrogen should be increased to the check further mortality, by integrated field management strategies.